2014
DOI: 10.1007/s40263-014-0142-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of N-Acetylcysteine in the Management of Substance Use Disorders

Abstract: There is a clear and pressing need to expand pharmacotherapy options for substance use disorders (SUDs) in order to improve sustained abstinence outcomes. Preclinical literature has demonstrated the role of glutamate in addiction, suggesting that new targets for pharmacotherapy should focus on the restoration of glutamatergic function. Glutamatergic agents for SUDs may span multiple addictive behaviors and help demonstrate potentially overlapping mechanisms in addiction. The current review will focus specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 96 publications
2
116
0
1
Order By: Relevance
“…NAC appears to restore normal glutamate signaling and decrease reinstatement of heroin, cocaine, and nicotine seeking in animal models (16-22). Clinical data also support the efficacy of NAC as a pharmacotherapy to reduce compulsive behavior (23) and reverse addiction pathology (24, 25). Preliminary data with cigarette smokers has demonstrated that NAC reduces smoking and smoking-related reward (17, 26).…”
Section: Introductionmentioning
confidence: 81%
“…NAC appears to restore normal glutamate signaling and decrease reinstatement of heroin, cocaine, and nicotine seeking in animal models (16-22). Clinical data also support the efficacy of NAC as a pharmacotherapy to reduce compulsive behavior (23) and reverse addiction pathology (24, 25). Preliminary data with cigarette smokers has demonstrated that NAC reduces smoking and smoking-related reward (17, 26).…”
Section: Introductionmentioning
confidence: 81%
“…Markou's group did not test below 30 mg/kg. While precise cross-species and cross-paradigm comparisons are difficult, taking these data together is promising and potentially clinically relevant given that humans generally tolerate N-acetylcysteine well (Deepmala et al 2015; McClure et al 2014). N-acetylcysteine has also been shown to reduce cocaine- (Baker et al 2003), heroin-(Zhou and Kalivas 2008), and nicotine-seeking (Ramirez-Nino et al 2013) behavior in laboratory models and efficacy in some substance abuse clinical trials (Deepmala et al 2015; McClure et al 2014; Knackstedt et al 2009) including a reduction in the number of cigarettes smoked by daily smokers (Knackstedt et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the potential utility of N-acetylcysteine to reduce cocaine seeking enhanced by coexisting depression was demonstrated (Frankowska et al, 2014). These findings suggest a potential treatment option for long-term application (Asevedo, Mendes, Berk, & Brietzke, 2014;McClure, Gipson, Malcolm, Kalivas, & Gray, 2014), although further studies will be needed to test this hypothesis.…”
Section: N-acetylcysteinementioning
confidence: 97%